The psychometric properties of the Coleman Dog Attitude Scale and Owner-Pet Relationship Scale-Modified : a South African study - Esterhuyzen, Mia (Stellenbosch : Stellenbosch University., 2020)
Thesis (MA)--Stellenbosch University, 2020.